P–281 Is it worth to go to blastocyst when there are less than 4 embryos on day 3?. (6th August 2021) - Gonzale. Marti, B; Pessah, C; Entezami, F
Abstract: Study question: Are pregnancy rates similar with blastocyst transfer compared to D3 transfer for patient with a poor embryo yield. Summary answer: In poor prognosis patients, more D3 embryos are needed to result in similar outcome compared to single blastocyst and it increases the multiple pregnancy risk. What is known already: Good prognosis patients benefit from a blastocyst transfer rather than cleavage-stage embryo because day 3 morphology has limited predictive value for subsequent developmental. A Cochrane meta-analysis in 2016 found a higher live birth rate per transfer in the blastocyst group compared to cleavage-stage and no difference in miscarriage and multiple pregnancies. However, in unselected patients, studies have yielded conflicting results and especially in poor prognosis patients at risk of transfer cancellation. A threshold of four good embryos on the third day has been previously correlated with blastocyst yield and live birth rate compared with cleavage-stage embryo transfer. Study design, size, duration: We analyzed the outcome of 1115 cycles with less than 4 embryos during 2019–2020 and compared the results between two groups of D3 and D5 transfers. Participants/materials, setting, methods: Amongst 1115 study cycles, in 691 cycles a D3 transfer was performed and in 424 cycles a D5 transfer was performed. We compared transfer cancellation rates, mean number of transferred embryos and ongoing pregnancy rates between the two groups and also in subgroups with female age <37 and female age >37. The statistical analyses were done by Chi square and t-test for paired samples. Main results and the role of chance: In the overall study population, the mean female age was 36.3 ± 4.3 years, the mean number of obtained embryos was 2.4 ± 1.0, the mean number of transferred embryos was 1.4 ± 0.8. 17.2% of the cycles resulted in transfer cancellation (6.2% in D3 transfer group and 35.0% in D5 transfer group). After D3 transfer the ongoing pregnancy rate (OPR) per transfer was 21.5% compared to 39.7% in D5 transfers (p < 0.05). A similar pattern was observed in subgroups of age <37 years and >37 years with OPR per transfer significantly higher when D5 transfer was performed. Notably more embryos were transferred on D3 compared to D5 (mean number 1.4 for D3 and 1 for D5). Nonetheless, OPR were similar per cycle in both groups and subgroups of different ages. Limitations, reasons for caution: A prospective randomized controlled trial is needed to confirm these results that are consistent with previously reports on retrospective and observational studies. Wider implications of the findings: In poor prognosis patients with low embryo yield, D3 and D5 transfers result in similar OPR per cycle. Transferring at blastocyst stage is not inferior to D3, despite the high cancellation rate, and appears safer permitting a single embryo transfer to avoid multiple pregnancy. Trial registration number: Not applicable